The development of the theory of sovereignty and the modern law of nations from Machiavelli to Grotius - BÜYÜK, MEHMET EMİN (My University, 2022)
Political thought that continued until the Middle Ages, has been transformed both in the field of sociology and politics and in the theoretical field, alongside modernity. The keyword for this transformation is sovereignty. Sovereignty brings the relationship between auctoritas and potestas, which was previously sought in an external source, to a mundane level. Machiavelli was one of the first to see this change and went beyond a priori judgments brought by medieval political thought, leaving it to Bodin to replace the legitimacy relationship that he destroyed. Sovereignty is an inherent element of the state. It is absolute, perpetual, one, and indivisible. A true sovereign is one who possesses all these. Ultimately, basing legitimacy on a divine source-which was the missing point in Bodin\"s definition of the secular state- became a component of the framework drawn by Suarez, which was based on the social contract theory. The modern states that emerged manifested their sovereignty in various ways, both internally and externally. The relations of such sovereign structures with each other achieved order within the system of international law. Vitoria foresaw modern international law regulating such a relationship between equals. Suarez rethought the facts seen by his predecessor with a positivist interpretation. Grotius took his place as the founder of modern international law by systematizing these previous interpretations. The current structure of international law is based on this background.

Orta Çağ’a kadar gelen siyaset düşüncesi, moderniteyle birlikte hem sosyoloji ve siyaset alanında hem de teorik alanda dönüşüme uğramıştır. Bu dönüşümün anahtarı olan kelime egemenliktir. Egemenlik, daha önce dışsal bir kaynakta aranan yasa ile uygulama arasındaki ilişkiyi dünyevi bir düzleme indirecektir. Machiavelli bu değişimi en önce görenlerdendir ve Orta Çağ siyaset düşüncesinin getirdiği a priori yargıların dışına çıkar. Onun yıktığı meşruiyet ilişkisi yerine yenisini koymak ise Bodin’e düşecektir. Egemenlik, devletin özünde var olan bir unsurdur. Mutlaktır, süreklidir, bir ve bölünmezdir. Gerçek bir egemen bu unsurların tümüne sahip olandır. Bodin’in düşüncesindeki laik devletin tanımlanmasında eksik nokta olan, nihai olarak meşruiyetin Tanrısal bir kaynağa dayandırılması ise, Suárez’in sosyal sözleşme kuramı temelli çizdiği çerçeve ile yetkinleştirilecektir. Böylece ortaya çıkan modern devletler içeriye ve dışarıya karşı egemenliklerini çeşitli biçimlerde ortaya koyar. Bu türden egemen yapıların birbiriyle ilişkisi ise devletler hukuku sistemi içerisinde bir düzene kavuşur. Bu türden bir eşitler arasındaki ilişkiyi düzenleyen modern uluslararası hukuku ise Vitoria önceden görmüş; Suárez selefinin gördüğü olguları pozitivist bir yorumla yeniden düşünmüş; Grotius da kendisinden önceki yorumları sistematikleştirerek modern devletler hukukunun kurucusu olarak yerini almıştır. Uluslararası hukukun bugün halen geçerli olan yapısı bu arkaplana dayanmaktadır.
Machiavelli’den Grotius’e egemenlik kuramının ve modern devletler hukukunun gelişimi
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Hukuk; Social Sciences and Humanities; Sociology; Law; HUKUK; Sosyal Bilimler Genel; Sosyal Bilimler (SOC); LAW; SOCIAL SCIENCES, GENERAL; Social Sciences (SOC); Genel Sosyal Bilimler; Hukuk; Sosyal Bilimler ve Beşeri Bilimler; General Social Sciences; Social Sciences & Humanities; Sovereignty; Modern State; Modernity; Law of Nations; International Law; Machiavelli; Vitoria; Bodin; Suarez; Grotius; Egemenlik; Modern Devlet; Modernite; Devletler Hukuku; Uluslararası Hukuk; Machiavelli; Vitoria; Bodin; Suárez; Grotius; Sovereignty; Modern State; Modernity; Law of Nations; International Law; Machiavelli; Vitoria; Bodin; Grotius